Global and regional diabetes prevalence estimates for 2019 and projections for 2030 and 2045: Results from the International Diabetes Federation Diabetes Atlas, 9th edition. (November 2019) - Saeedi, Pouya; Petersohn, Inga; Salpea, Paraskevi; Malanda, Belma; Karuranga, Suvi; Unwin, Nigel; Colagiuri, Stephen; Guariguata, Leonor; Motala, Ayesha A.; Ogurtsova, Katherine; Shaw, Jonathan E.; Bright, Dominic; et al.
Abstract: Aims: To provide global estimates of diabetes prevalence for 2019 and projections for 2030 and 2045. Methods: A total of 255 high-quality data sources, published between 1990 and 2018 and representing 138 countries were identified. For countries without high quality in-country data, estimates were extrapolated from similar countries matched by economy, ethnicity, geography and language. Logistic regression was used to generate smoothed age-specific diabetes prevalence estimates (including previously undiagnosed diabetes) in adults aged 20–79 years. Results: The global diabetes prevalence in 2019 is estimated to be 9.3% (463 million people), rising to 10.2% (578 million) by 2030 and 10.9% (700 million) by 2045. The prevalence is higher in urban (10.8%) than rural (7.2%) areas, and in high-income (10.4%) than low-income countries (4.0%). One in two (50.1%) people living with diabetes do not know that they have diabetes. The global prevalence of impaired glucose tolerance is estimated to be 7.5% (374 million) in 2019 and projected to reach 8.0% (454 million) by 2030 and 8.6% (548 million) by 2045. Conclusions: Just under half a billion people are living with diabetes worldwide and the number is projected to increase by 25% in 2030 and 51% in 2045.